Do hysterectomy techniques affect sexual functions and lower urinary system complaints? - Aydoğan Kırmızı, Demet; Başer, Emre (Journal of Surgery and Medicine, 2020)
Aim: Hysterectomy is the most common gynecological surgical procedure. Therefore, detailed consultation about the postoperative effects of hysterectomy is an integral part of the operation. However, available data on these issues are limited and conflicting. The aim of this study is to evaluate the effects of hysterectomy types on lower urinary tract symptoms (LUTS), sexual function and quality of life. Methods: Patients between 38-60 years of age who underwent total laparoscopic hysterectomy (TLH), vaginal hysterectomy (VH), and, in addition to standard total abdominal hysterectomy (TAH), uterosacral ligament-cuff suturing operation between June 2017 and 2019 were included in this cross-sectional study. Urgency, urge incontinence, frequency, abnormal emptying, hesitancy, nocturia, overflow, and interrupted stream are considered LUTS symptoms. Sexual functions were evaluated by Index of Female Sexual Function Index (FSFI) and the quality of life was evaluated by the EQ-5D (European Quality of Life Five- Dimension Scale) during the post-operative period. Results: There was a significant decrease in urgency, urge incontinence, frequency, abnormal emptying, nocturia and interrupted stream symptoms (P<0.05) in the VH group (n=30), and urge and urge incontinence symptoms in TAH group (n=213) (P<0.05) postoperatively. In terms of the FSFI total score, the highest sexual dysfunction was in the TAH group whereas the lowest was in the TLH (n=60) group. Conclusions: Hysterectomy does not worsen LUTS. The best post-operative sexual functions were found in the TLH group. The post-operative quality of life was better in patients operated vaginally and laparoscopically.